Web-Based Patient Service Information System at AL-Furqon Health Clinic, Palembang - Arum Adisha Putra Anandez; Agustina Heryati; Abdul Kholik (CV. AFDIFAL MAJU BERKAH, 2026)
AL-Furqon Health Clinic is a healthcare facility committed to providing quality and affordable medical services to the community. However, the manual management of patient data often leads to delays in record-keeping, risk of data loss, and suboptimal service delivery. This study aims to design and develop a web-based patient service information system that supports patient registration, data management, service scheduling, and medical record documentation in an integrated manner at AL-Furqon Clinic Palembang. The system was developed using the Agile method and Unified Modeling Language (UML) modeling to represent system requirements and workflows. The technologies used include JavaScript, MySQL, and XAMPP. This web-based patient service information system integrates and manages registration, reservations, medical records, and service schedules in real-time, providing convenience for patients to access services online and assisting administrators and medical staff in efficiently managing data and services. The research results indicate that the system improves efficiency, accuracy, and speed in managing patient service data. With this system, healthcare services at AL-Furqon Clinic are expected to become more effective and well- structured.